Confinement of paraffin in organophilic layered silicate clay as thermal energy storage system - Alamani, Bryan Gencianeo (2012)
Thermal energy storage (TES) is one of the important technologies for waste heat recovery and energy efficiency. Phase change nanocomposite (PCN) is one of the most promising TES in particular for large scale application. Form-stable PCN comprising of inorganic smectite clay, polymer and paraffin was prepared by one pot step wise interrelation. The resulting nonocomposite was found to confine the paraffin in the interlayer of the expanded organophilic layered silicate clay as determined by XRD and TEM. XRD results revealed high basal spacing expansion of the clay from 12 Å to 71-98 Å. Furthermore, some of the nanocomposites showed expansion beyond the detection limit of XRD and were further evaluated via TEM. Basal spacing measurements observed from TEM images are consistent with the prediction of the calculated basal spacing using Bragg?s Law based on the XRD data. In addition, FTIR has supported the results of XRD and TEM describing the clay morphology as exfoliated or intercalated. The phase change nanocomposites were found to be thermally stable as revealed by TGA. The thermal properties associated with latent heat thermal energy storage capacity namely latent heats of fusion and crystallization, as well as phase transition temperatures were evaluated by DSC and found to meet basic requirements for thermal energy storage systems. The surface morphology was observed via SEM. The phase change nonocomposite was found to be form-stable which may be attributed to the confinement of the paraffin in the interlayer of the clay Keywords: thermal energy storage, intercalated clay composite, intercalation, sodium montmorillonite, phase change material